Nota sôbre um possível fator sub-letal em gado Holstein-Friesian - Jardim, W. R.; Peixoto, A. M. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1950)
In this note the A. A. relate the occurrence of a possible sub-lethal factor, on the Holstein-Friesian herd of Escola Superior de Agricultura "Luiz de Queiroz", Piracicaba. The sire Horto was mated with his own mother, Brisa, and so, were obtained two calves, a male and a female, consecutively. Both the calves presented flexion and deviation of the fore legs. The sire's death has not alloved further observations. The study of these history cases excludes the mother's nutritional deficiency, as the cause of related phenomenon. In the consulted literature, VEIGA and MEAD et al. relate similar cases, although these are observed in other breeds of cattle The A. A. admit that cause of occurrence is a possible sublethal recessive factor, put in evidence by inbreeding.